Programming experiment course for innovative and sustainable education: A case study of Java for Millikan Oil-Drop experiment - Li, Yizheng; Su, Guandong; Pan, Haocheng; Tan, Chengwei; Li, Gongsheng (Journal of cleaner production, 2024)
A teaching approach of programming experiment courses with a new education process is proposed in this study to improve the sustainability of engineering education and extend the accessibility of lab experiments across experiment courses, with the goal of encouraging innovative and scientific thinking among students. The Millikan Oil-Drop experiment combined with Java object-oriented programming is demonstrated as a case study to validate the feasibility and advantages of this teaching approach. The new education process of the experiment course is designed based on Jean Piaget's cognitive development theory, which has high practical potential for popularization among tertiary institutions without additional cost. Additionally, this work discussed the relevance of the general criterion of the Accreditation Board for Engineering and Technology on student outcomes to educational accreditation, further indicating that introducing programming into experiment education can improve students' all-round ability and strengthen the triangular relationship among the three main subjects in tertiary education, namely, students, faculty, and higher educational institutions. This study may serve as an educational guide for teachers and tertiary institutions to pursue innovative and sustainable education. [Display omitted] •Introducing programming to course can enhance sustainability for education.•Programming can help students facilitate the data-processing of experiments.•Introducing programming can better ignite students' interest in the course.•The innovation-oriented approach can help improve the teaching quality.•The approach can make for clean production and sustainable development.